"Nós lutamos por dignidade. Quem não luta por seus direitos" : trabalhadoras domésticas em contexto de pandemia de covid-19 na cidade de São Luís-Maranhão - Barros, Luriana de Sousa (2022)
This work addresses the conditions established for paid domestic workers during the Covid-19 pandemic, in the city of São Luís do Maranhão (Brazil), starting with the declaration, in March 2020, of the health emergency situation, until July 2022. From the perspective of the anthropology of health and the theoretical contribution of black and decolonial feminist thought, this research addressed how the experiences of this professional category, historically vulnerable, took place in the context of living with a contagious disease and its evolution uncertain, which caused numerous impacts on health and on the organization of people's daily lives, although in a different way and with equally different intensities, considering the temporality of the pandemic with its curves of deaths and new infections. The methodology included visits to the Union of Domestic Workers of Maranhão (Sindoméstico-MA), participation in activities and semi-structured interviews carried out with the women who currently guide this space and workers who are not unionized, but who use the services offered by the union. This space was the gateway to making contact with women domestic workers and one of the privileged fields of observation. The claim for the guarantee of labor rights emerged in an evident way in the fieldwork. It was possible to observe, in a more accentuated way, in the pandemic context, the lack of access to social security - a set of public policies initiated by the Public Authorities, whose duty is to ensure access to rights related to health, social security and social assistance -, which called our attention to think about the precariousness of the working conditions established for paid domestic workers in the current scenario. The research also made it possible to access the memory of the trajectories, experiences and narratives of the life of domestic workers in São Luís do Maranhão.